2014
DOI: 10.1111/1755-0998.12304
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding gap: reliable species identification over morphological and geographical scales

Abstract: The philosophical basis and utility of DNA barcoding have been a subject of numerous debates. While most literature embraces it, some studies continue to question its use in dipterans, butterflies and marine gastropods. Here, we explore the utility of DNA barcoding in identifying spider species that vary in taxonomic affiliation, morphological diagnosibility and geographic distribution. Our first test searched for a 'barcoding gap' by comparing intra- and interspecific means, medians and overlap in more than 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 78 publications
3
138
1
1
Order By: Relevance
“…material 4). We sequenced a fragment of the mitochondrial ‘DNA barcode’ Cytochrome c oxidase subunit 1-COI, a useful marker at low taxonomic levels in spiders, to establish boundaries among species (Čandek and Kuntner 2015; Hebert et al 2003). To amplify COI we used the primers LCO 1490 and HCO 2198 (Folmer et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…material 4). We sequenced a fragment of the mitochondrial ‘DNA barcode’ Cytochrome c oxidase subunit 1-COI, a useful marker at low taxonomic levels in spiders, to establish boundaries among species (Čandek and Kuntner 2015; Hebert et al 2003). To amplify COI we used the primers LCO 1490 and HCO 2198 (Folmer et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Work on this group has demonstrated the efficacy of DNA barcoding in identifying known species (Wilson et al 2013;Dinca et al 2015) and in revealing cryptic species complexes (Burns et al 2008;Huemer et al 2014a). It has also shown that there is very limited geographic variation in barcode sequences in populations of most species, so increased geographic scale does not reduce the success of species identification (Lukhtanov et al 2009;Huemer et al 2014b, Candek andKuntner 2015). However, in certain groups, such as diving beetles of the tribe Agabini (Bergsten et al 2012), the correlation between genetic and geographic distances is strong enough to impact the success of species identification unless sampling of each species is fairly comprehensive.…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Paucity of specimens of some species prevented establishing a ‘barcoding gap’ (e.g. Čandek and Kuntner 2015) but for the most closely related species that have multiple specimens available all are separated by a gap of >10 times greater inter- than intraspecific genetic distances (Table 1). All types are deposited in the National Museum of Natural History, Smithsonian Institution (NMNH).…”
Section: Methodsmentioning
confidence: 99%